Effect of Earnings Ability on Financial Performance of Savings and Credit Societies in Kenya - Muturi, Prof. Willy; Barus, Jane J.; Kibati, Dr. Patrick; Koima, Dr. Joel (International Journal of Finance and Accounting, 2017)
Purpose: The purpose of this study was to establish the effect of earnings ability on financial performance of savings and credit societies in Kenya. Methodology: The study employed an explanatory research design. The target population was 83 registered deposit taking SACCO's in Kenya that have been in operation for the last five years. The sample size for the study was all 83 SACCOs that have remained in existence since 2011-2015. Census methodology was used in the study. Both primary and secondary sources of data were employed. Multiple linear regression models were used to analyze the data using statistical package for the social sciences (SPSS) and STATA. A pilot study was conducted to measure the research instruments reliability and validity. Descriptive and inferential analysis was conducted to analyze the data. The data was presented using tables and graphs. Results: Based on the findings the study concluded that earnings ability influenced the financial performance of savings and credit societies in Kenya. This can be explained by the regression results which showed that the influence was positive and also showed the magnitude by which earnings ability influenced the financial performance of savings and credit societies. The univariate regression results showed that earnings ability influenced the financial performance of savings and credit societies by 6.438units. Unique contribution to theory, practice and policy: The study recommended for continuous review of credit policies, establishment of irrecoverable loan provision policies, development of sound staff recruitment policies and the use of appropriate financing mix. Further, the Government should review legal framework to ensure that institutional capital is used to grow SACCO's' wealth.